Relação entre queixa de memória, alterações cognitivas, autopercepção da saúde e ADAM10, em idosos - Almeida, Mariana Luciano de (2016)
There is a wide divergence of results in the literature on the clinical relevance and the etiology of memory complaints (MC). Currently QM is being studied as pre-clinical symptom of Alzheimer's disease before a possible CCL setting. Our hypothesis is that MC may be associated with lower performance on cognitive tests or a low self-rated health. Objective. To investigate the relationship among MC in elderly patients with objective cognitive impairment and self-rated health. Method. This was a cross-sectional, correlational and quantitative study. The instruments used were the Memory Complaint Scale (MCS) - forms A and B, Addenbrooke’s Cognitive Examination – Revised (CEA-R), Mini-Mental State Examination (MMSE), Clock Drawing Test (CDT), Medical Outcomes Study 8-item Short-Form Heath Survey, Geriatric Depression Scale and a sociodemographic questionnaire. Results. Participated in this study 83 subjects, divided between the two forms of MCS evaluation scale. Sociodemographic groups were very similar, with no significant differences with MC. According to MCS-A, there was a significant association only with the CDT. MCS-B was associated with ACE-R and its domains memory, fluency and visual spatial orientation?. A ROC curve was drawn from the results of MCS-B in relation to the ACE-R and MMSE, demonstrating the high specificity of the instrument. Conclusion. In this study it was not found robust results with MC reported by the elderly and changes in cognitive screening tests. However, when the informant reported the complaint, the analysis with cognitive performance levels were more consolidated. This results highligh the need to include and empower perception of someone who knows enough the elderly to assess the MC globally.